Sexual function in women using Depo- medroxy Progesterone Acetate (DMPA) - Dolatian, mahrokh; Sheikhan, zohreh; Simbar, masoumeh; Ozgoli, Giti; Noori, mohammad; Nasiri, malihe; Khoramabadi, monirasadat; Kavousi, fahimeh (Advances in Nursing & Midwifery, 2015)
Background and aim: Sexuality is an important aspect of quality of life that affects both physical and psychological aspects. Sexual relationship is central to quality of women’s life, and reflects her psychosocial and life aspects. Different factors such as health, emotional problems, stress, and hormones affect sexual function. Some reports reveal the effect of hormones, and conversely, some report lack of effect. This study aimed to asses sexual function of women using DMPA presenting to health centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran , Iran in 2013 Methods and material : This descriptive study was conducted on 120 women in health centers in Tehran, Iran. They were selected by multistage sampling. A questionnaire completed by interviewing was used for data collecting. 3 parts were included in the questionnaire: demographic characteristic, and Female Sexual Function Index (FSFI). Data was analyzed by SPSS 16 and Different statistical tests were used. (P<0. 05) Result: Mean age of women was 28. 63±7. 16 years. Women use DMPA had favorite sexual function (60. 8%). Logistic regression showed women with regular menstruation had favorite sexual function than others (P<0. 05) . Conclusion: Menstrual patterns was significantly associated with sexual function.While introducing hormonal contraceptive methods, health workers should emphasize their adverse effects such as menstrual patterns on sexual function. Key word: Sexual function, Depo-medroxy Progesterone Acetate, Prevalence, Iran.